Curvature determination of embedded silicon chips by in situ rocking curve X-ray diffraction measurements at elevated temperatures. Issue 4 (28th September 2016) - Angerer, Paul; Schöngrundner, Ronald; Macurova, Katerina; Wiessner, Manfred; Keckes, Jozef
Abstract : The deflection (curvature) of embedded single-crystal silicon chips was investigated by rocking curve X-ray diffraction techniques at two significant manufacturing stages in the process chain of printed circuit boards with embedded components. An overview of the curvature deduction by two different approaches was presented: (1) the measurement of the variation of the rocking curve maximum as a function of the lateral sample position along a specific traverse; the slope in such a diagram is then proportional to the corresponding curvature in that direction. (2) The evaluation of the rocking curve width; here the peak width is inversely proportional to the curvature at known beam diameter, diffraction angle, and beam divergence. It was shown that the rocking curve method is applicable to determine the curvature inside single crystalline chips. Furthermore, the method is also suitable to determine the curvature of fully embedded or encapsulated chips. Additionally the absorption of the radiation in the embed medium was quantitatively discussed. The curvature of two different prepared samples was determined at temperatures up to 200 °C in a heating stage attached to the diffractometer device.